Our First Experience Implementing "Clinical Embryology and Reproductive Medicine" as a Curriculum Course of the Study Program General Medicine at the Faculty of Medicine in Bratislava, Slovakia - Varga, Ivan; Lapides, Lenka; Brucknerová, Ingrid; Gálfiová, Paulína; Visnyaiová, Kristína; Csöbönyeiová, Mária; Klein, Martin; Žiaran, Stanislav; Sysák, Rastislav; Záhumenský, Jozef (Physiological research, 2022)
There is no separate course in the medical curriculum summarizing all aspects of human reproduction in most medical school curricula. At the same time, such a course would logically connect knowledge from clinical embryology and assisted reproduction, encompassing the issue of female and male infertility, mechanisms of birth defect formation, their prenatal diagnosis and subsequent specialized neonatal care. The aim of a wide team of university teachers comprising embryologists, gynecologists, neonatologists, endocrinologists, geneticists and others was to create and implement a new course entitled "Clinical Embryology and Reproductive Medicine" into the fourth-year curriculum of the study program General Medicine at the Faculty of Medicine, Comenius University in Bratislava. There has been a great interest in the course, as evidenced by the number of medical students enrolled. The lecture syllabuses have been divided into several thematic areas: 1) Clinical embryology including a laboratory part of assisted reproduction, 2) Cause and treatment options of female and male infertility, 3) A comprehensive view of the issue of birth defects, 4) The issue of preconception education, prenatal and childbirth training, family planning, 5) Reproductive immunology and endocrinology. Despite the complexity of human reproduction being a mainstay of gynecology and obstetrics, it is underemphasized in the medical school curricula worldwide. It is often reflected in shorter hospital / practical trainings during undergraduate studies and lower requirements at the final exam. Therefore, as students almost unanimously valued, this new course is extremely helpful in preparing for the final state exam.
Keywords: Female; Faculty; novorozenec; ženské pohlaví; Slovakia; lidé; Infant, Newborn; těhotenství; Students, Medical; Curriculum; reprodukční lékařství; studenti lékařství; Infertility, Male; Male; akademický sbor; kurikulum; Slovenská republika; Reproductive Medicine; mužské pohlaví; mužská infertilita; Pregnancy; Humans